HUBUNGAN ANTARA KECERDASAN SPIRITUAL DENGAN KOMPETENSI SOSIAL GURU TK DI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Fitri Yenti Yenti; Wilson '; Nurlita ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: In this study the author intends to examine two variables to determine whether there is a relationship between the independent variable (X) with the dependent variable (Y). The population of this study is the entire kindergarten teacher in District Kuantan Singingi forth as many as 50 kindergarten teachers. As for testing purposes researchers took samples from the Kuantan Tengah District of 20 kindergarten teachers. Based on the observations of the author while in some kindergarten teachers in the district Kuantan Kuantan Singingi Mudik found symptoms or phenomena, among others, relating to the social competence of teachers: the existence of some teachers who communicate and interact with students in a way that is less mannered, their most teachers are less adapted to their assigned (like bored with the state of the school). And of spiritual intelligence discovered phenomena: the existence of some teachers who use that language are not appropriate when angry to students who are not able to answer the teacher's question, a sense of caring and empathy of teachers to the school and its work is still lacking. From the research results can be seen on the Kolmogorov-Smirnov column can be seen that the value of significance for spiritual intelligence (0.200) and social competence (0.200); Because of the significance of all variables is greater than 0.05, it can be concluded that the data on the variables of spiritual intelligence and social competence normal distribution, homogeneity test analysis results, obtained statistical values of 0.834 and a probability value of 0608. Since the value of p> 0.05 (0608> 0.05) then the data is homogeneous, and the coefficient of determination is generated is equal to r2 = 0217, p = 0.001 (p <0.05), it can be seen that the influence of spiritual intelligence 21.7% of the social competence of teachers. Then concluded There is a relationship between the spiritual intelligence with Social Competence kindergarten teacher at Regency Kuantan District Mudik Singingi. Key word: Spiritual Teacher With Social Competence